Improving the regular management of the state budget in Cai Nuoc district, Ca Mau province - Ha, Thúc Vĩnh Duy (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Reasonable allocation and use of state budget resources is an important issue for administrative and non-business units in order to improve the efficiency of state budget management. Based on basic theoretical issues on state budget expenditure management, the article assesses the current situation of state budget recurrent expenditure management at the People's Committee of Cai Nuoc district in the 2016-2020 period and proposes proposing key solutions to improve the management of recurrent state budget expenditures in the locality. The research results show that the management of recurrent expenditures of the state budget by the People's Committee of Cai Nuoc district is consistent with the local socio-economic situation, basically in compliance with the 2015 State Budget Law and guiding documents of Ca Mau province. However, besides the achieved results, the management of recurrent expenditures of the state budget in the district is still incomplete, wastefulness, and scattered spending still have pressing problems, hindering potentials. development capacity of the district.